1995
DOI: 10.1523/jneurosci.15-11-07712.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface morphology identifies microglia as a distinct class of mononuclear phagocyte

Abstract: To investigate differences among brain-derived microglia and other classes of immune cells, we compared the morphologies and growth properties of mononuclear phagocytes isolated from tissues of the newborn rat. Scanning EM shows that microglia from postnatal rat brain are covered with spines (typically > 20 per cell body) in a distinctive manner which contrasts the smooth surfaces of bone marrow cells and the ruffled surfaces of tissue macrophages from spleen, liver, and peritoneum. The spine-bearing surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 39 publications
(48 reference statements)
11
106
2
Order By: Relevance
“…1). These flow cytometric based observations are consistent with previous reports by Guilian and colleagues that microglia and macrophages isolated from CNS tissue can be distinguished by their differential size and density of cell processes [39]. These FACs and EM detectable differences in morphology of CNS-resident microglia and CNS-infiltrating macrophages are evident in ex vivo analysis.…”
Section: Is Microgliosis Another Name For Macrophage Infiltration Intsupporting
confidence: 91%
“…1). These flow cytometric based observations are consistent with previous reports by Guilian and colleagues that microglia and macrophages isolated from CNS tissue can be distinguished by their differential size and density of cell processes [39]. These FACs and EM detectable differences in morphology of CNS-resident microglia and CNS-infiltrating macrophages are evident in ex vivo analysis.…”
Section: Is Microgliosis Another Name For Macrophage Infiltration Intsupporting
confidence: 91%
“…Second, some markers that label macroglial cells have been reported also to label microglia (Dickson and Mattiace, 1989;Wolswijk, 1995). And third, microglial cells have features di erent from other cells of the mononuclear phagocytic system: they display particular morphological features in vitro (Giulian et al, 1995), proliferate spontaneously in culture (Giulian et al, 1995), and have a distinct ion channel pattern di erent from that of monocytes and macrophages in non-nervous tissues (Kettenmann et al, 1990;Brockhaus et al, 1993).…”
Section: Origin From Monocytes/macrophagesmentioning
confidence: 99%
“…At present, it is not known whether all cells of the macrophage/monocyte lineage can produce microglia cells, or whether this ability is limited to a special subset of such cells. Giulian et al (1995) found that mononuclear phagocytes isolated from the brain of newborn rats gave rise to cells with particular morphological features which did not appear in cultured mononuclear phagocytes from non-nervous sources; these authors concluded that microglial precursors are a unique class of cell di erent from precursors of other types of mononuclear phagocytes. In this connection, it was found that a subpopulation of bone marrow-derived cells showed the same ion channel pattern as microglial cells, suggesting that the bone marrow contains precursors that are committed to produce microglia and that they are di erent from the precursors which produce macrophages for other body regions (Banati et al, 1991).…”
Section: Origin From Monocytes/macrophagesmentioning
confidence: 99%
See 2 more Smart Citations